A comparison of American and English hospital discharge rates for pediatric bipolar disorder, 2000 to 2010. - James, A; Hoang, U; Seagroatt, V; Clacey, J; Goldacre, M; Leibenluft, E (2014)
OBJECTIVE: Controversy exists over the diagnosis and prevalence of pediatric bipolar disorder (PBD). Although several small surveys suggest that the rate of the PBD diagnosis in clinical settings is higher in the United States than in other countries, no comprehensive cross-national comparisons of clinical practice have been performed. Here, we used longitudinal national datasets from 2000 to 2010 to compare US and English hospital discharge rates for PBD in patients aged 1 to 19 years. METHOD: We used the English National Health Service (NHS) Hospital Episode Statistics (HES) dataset and the United States National Hospital Discharge Survey (NHDS) to compare US and English discharge rates for PBD (bipolar I disorder [BP-I], bipolar II disorder [BP-II], bipolar disorder not otherwise specified [BP-NOS], and cyclothymia). We also conducted cross-national comparisons for all other psychiatric diagnoses in youth and for adults with bipolar disorder (BD). RESULTS: There was a 72.1-fold difference in discharge rates for PBD in youth between the United States and England (United States, 100.9 per 100,000 population, 95% confidence interval = 98.1-103.8, versus England, 1.4 per 100,000 population, 95% CI = 1.4-1.5). After controlling for cross-national differences in length of stay, discharge rates for PBD remained 12.5 times higher in the United States than in England. For all other child psychiatric diagnoses, the discharge rate was 3.9-fold higher, and for adults with BD 7.2-fold higher, in the United States than in England. CONCLUSION: The disparity between US and English discharge rates for PBD is markedly greater than the disparity for child psychiatric discharge rates overall and for adult rates of BD. This suggests that the difference in discharge rates for PBD may be due to differing diagnostic practices for PBD in the United States versus in England.